1994
DOI: 10.1108/eb008626
|View full text |Cite
|
Sign up to set email alerts
|

Wine: Achieving Competitive Advantage Through Design

Abstract: Considers the role of design as a marketing tool for the wine industry. The meaning of design and its relationship to marketing is defined then explored from a number of perspectives to demonstrate its relevance to modern wine making techniques. Examines the possibilities for a design led approach to wine making using case material from an English Winery. Concludes that design offers real opportunities in wine making as a means for developing effective marketing strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 3 publications
1
33
1
1
Order By: Relevance
“…Barber, Almanza, and Donovan (2006), and Barber and Almanza (2006) found that many consumers feel intimidated by aspects of wine packaging, such as the information placed on labels. Barber and Almanza (2006) also refer to previous studies (Jennings & Wood, 1994;Chaney, 2000;Bloch, Brunel, & Arnold, 2003) that identified the importance of the packaging of wine bottles as a key component in the promotion and consumption of wines. These issues, while not directly linked to product imagery may, however, have direct implications for ways in which consumers view the wine product.…”
Section: Conclusion Limitations Implications and Future Researchmentioning
confidence: 92%
“…Barber, Almanza, and Donovan (2006), and Barber and Almanza (2006) found that many consumers feel intimidated by aspects of wine packaging, such as the information placed on labels. Barber and Almanza (2006) also refer to previous studies (Jennings & Wood, 1994;Chaney, 2000;Bloch, Brunel, & Arnold, 2003) that identified the importance of the packaging of wine bottles as a key component in the promotion and consumption of wines. These issues, while not directly linked to product imagery may, however, have direct implications for ways in which consumers view the wine product.…”
Section: Conclusion Limitations Implications and Future Researchmentioning
confidence: 92%
“…Some considered the recognizability of individual products to be positive, while others believed that the individualism predominant in the Merlot Ticino production system is negative because it can create obstacles to the recognition of the Merlot Ticino brand. Similar considerations held for the shape of labels, which-in the vast majority of cases (70 percent of respondents to the content analysis)-were different from the traditional dimensions of European red wines (Jennings and Wood, 1994). …”
Section: Communication Channelsmentioning
confidence: 99%
“…Such "reassuring" packaging elements for wines are those designed in a traditional manner, following the approaches of the European wine tradition. For instance, the bordelaise bottle for red wines and the cork seals suggest tradition (Jennings and Wood, 1994;Murray and Lockshin, 1997). Meanwhile, innovative and experimental designs may appear threatening to consumers, or they may induce curiosity or a sense of adventure (Cox and Cox, 1988), so they tend to be appreciated by consumers who seek novel experiences (Veryzer and Hutchinson, 1998).…”
Section: Projection: Textual Narration and Visual Communicationmentioning
confidence: 99%
See 2 more Smart Citations